A Meta-Analysis of Risky Sexual Behaviour among Male Youth in Developing Countries - Yifru Berhan; Asres Berhan (AIDS Research and Treatment)
The purpose of this meta-analysis was to assess the association between risky sexual behaviour and level of education and economic status in male youth. Previous tests of the association of risky sexual behaviour with levels of education and economic status have yielded inconsistent results. Using data from 26 countries, from both within and outside Africa, we performed a meta-analysis with a specific focus on male youths’ risky sexual behaviour. We applied a random effects analytic model and calculated a pooled odds ratio. Out of 19,148 males aged 15–24 years who reported having sexual intercourse in the 12 months preceding the survey, 75% engaged in higher-risk sex. The proportion of higher-risk sex among male youth aged 15–19 years was nearly 90% in 21 of the 26 countries. The pooled odds ratio showed a statistically significant association of higher-risk sex with male youth younger than 20 years, living in urban centers, well educated, and of a high economic status. The overall proportion of condom use during youths’ most recent higher-risk sexual encounter was 40% and 51% among 15–19-year-olds and 20–24-year-olds, respectively. Our findings suggest that male youth’s socioeconomic status is directly related to the likelihood that they practice higher-risk sex. The relationship between income and sexual behaviour should be explored further.